Hepatic stellate cell as a Mac‐2‐binding protein‐producing cell in patients with liver fibrosis. Issue 10 (29th April 2021) - Gantumur, Dolgormaa; Harimoto, Norifumi; Muranushi, Ryo; Hoshino, Kouki; Batbayar, Chingun; Hagiwara, Kei; Yamanaka, Takahiro; Ishii, Norihiro; Tsukagoshi, Mariko; Igarashi, Takamichi; Watanabe, Akira; Kubo, Norio; et al.
Abstract: Background: Mac‐2 binding protein (M2BP) glycosylated isomer (M2BPGi) is a serum marker of liver fibrosis; M2BPGi is a glycosylated form of M2BP. Hepatocytes and hepatic stellate cells (HSCs) have been studied to determine the source of M2BP. This study proposes to identify the origin of M2BP in fibrotic liver. Methods: Using liver fibrosis tissue specimens from 15 patients with liver cancer, M2BP mRNA and M2BP were detected by in situ hybridization and immunohistochemistry, respectively. The expression levels of M2BP mRNA were evaluated with scores of 3, 2, and 1. Fluorescent in situ hybridization was carried out to evaluate the distribution of M2BP mRNA and the activated‐HSC marker αSMA mRNA; multicolor fluorescent immunohistochemistry was used for protein localization of M2BP, α SMA, and CD68. The Kruskal–Wallis test analyzed the relationship between M2BP mRNA expression and existing serum fibrosis markers. Results: M2BP mRNA was expressed in spindle‐shaped cells along the fibrous septa and in the perisinusoidal area of the fibrotic liver. The HSC markers αSMA mRNA and M2BP mRNA were colocalized in the spindle‐shaped cells; on the protein level, M2BP was expressed in Kupffer cells. M2BP mRNA expression was positively correlated with serum M2BPGi levels. Aspartate transaminase‐to‐platelet ratio index, Fibrosis‐4, hyaluronic acid, and the 15‐minute indocyanine green retention rate were significantly correlated with M2BP mRNA expression. Conclusions: M2BP mRNA transcription in fibrotic liver was primarily observed in HSCs but not at the M2BP level, which suggests that HSCs might produce and introduce M2BP to Kupffer cells and serum.